Analisis Faktor yang Berhubungan dengan Penggunaan Produk Tembakau Non-Rokok pada Pelajar SMP di Indonesia - Ridhwan Fauzi; Siti Riptifah Tri Handari (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Non-cigarettes tobacco smoking products have similar negative impact to the health as conventional cigarettes.However, most of adolescent are unaware of the problem. Nowdays, the products gain more popularityamong youth. This study aims to find out factors associated with non-cigarettes tobacco products (NCTP) useamong junior high school students in Indonesia. The study used crossectional design. The source of data weresecondary data of the Global Youth Tobacco Survey (GYTS) 2014. GYTS is a school-based survey of junior highschool students. Data was obatianed from three regional (Jakarta, Bekasi, and medan) from September 21st 2013to June 20th2014. The population of study is national representative of junior high school students in Indonesia.The sampling method was multistage cluster random sampling. Total sampling was 5.986 students. Data wasweighted by SUDAN and analyzed by chisquare test and multiple logistic regressions. Study revealed that about3,6% respondents ever used NCTP in past 30 days. NCTC used was significantly associated with gender, conventionalcigarettes smoking status and attitude in p<0,001. Students who regularly smoked convenstional cigaretteswere 12,055 (CI 95%: 7,674-18,937) more likely to use NCTP than non smoker.